Current Challenges and Future Direction in Surveillance for Hepatocellular Carcinoma in Patients with Nonalcoholic Fatty Liver Disease - Cholankeril, George; El-Serag, Hashem B. (Seminars in Liver Disease, 2022)
The burden for hepatocellular carcinoma (HCC) attributed to nonalcoholic fatty liver disease (NAFLD) continues to grow in parallel with rising global trends in obesity. The risk of HCC is elevated among patients with NAFLD-related cirrhosis to a level that justifies surveillance based on cost-effectiveness argument. The quality of current evidence for HCC surveillance in all patients with chronic liver disease is poor, and even lower in those with NAFLD. For a lack of more precise risk-stratification tools, current approaches to defining a target population in noncirrhotic NAFLD are limited to noninvasive tests for liver fibrosis, as a proxy for liver-related morbidity and mortality. Beyond etiology and severity of liver disease, traditional and metabolic risk factors, such as diabetes mellitus, older age, male gender and tobacco smoking, are not enough for HCC risk stratification for surveillance efficacy and effectiveness in NAFLD. There is an association between molecular and genetic factors and HCC risk in NAFLD, and risk models integrating both clinical and genetic factors will be key to personalizing HCC risk. In this review, we discuss concerns regarding defining a target population, surveillance test accuracy, surveillance underuse, and other cost-effective considerations for HCC surveillance in individuals with NAFLD.
Keywords: liver cancer; cirrhosis; surveillance; guidelines; biomarkers; fatty liver